Assessment of facial and nasal phenotypes: implications in forensic facial reconstruction - Guleria, Ankita; Krishan, Kewal; Sharma, Vishal (Archives of Biological Sciences, 2025)
Paper description: Facial identification is a useful method in forensic examinations and biometric evaluations. The present study is an attempt to evaluate the phenotypes of face and nose based on facial and nasal indices in a North Indian population. Facial photographs and anthropometric measurements were taken for the assessment of facial and nasal indices. The faces and the noses were classified into five phenotypes based on standard numerical values of facial and nasal indices. The procedure is useful in biometric evaluations, forensic identification, facial recognition technology, and facial reconstruction as well as a reference to improving facial surgeries and rhinoplasty. Abstract: The present study is an attempt to evaluate the phenotypes of face and nose based on facial and nasal indices in a North Indian population. The study comprises 228 (158 males and 70 females) healthy, young, and adult participants ranging in age from 18 to 35 years. Facial photographs and anthropometric measurements were taken for the assessment of facial and nasal indices. The faces and noses were classified into five phenotypes based on standard numerical values of facial and nasal indices. The most common facial phenotypes were observed to be hypereuryprosopic (61 males, 38.60%, and 31 females, 44.28%), and euryprosopic (51 males, 32.27%, and 14 females, 20%). For the nasal phenotype, mesorrhine was most common among males (56.32%, 89]), while leptorrhine was predominant among females (55.71%, 39). The study's findings highlight facial variations and phenotype assessments that may aid forensic investigations, biometric evaluations, facial recognition technology, medico-legal applications, and facial reconstruction. Additionally, they serve as a valuable reference for enhancing facial surgeries and rhinoplasty. The study adds to the existing database of facial and nasal anthropometry for further use and comparison purposes.